Role of health literacy in an information society - CHRÁSKOVÁ, Marie (Journal of Education, Technology and Computer Science, 2014)
The paper addresses the role of health literacy in a contemporary informationsociety. Specifically, the paper defines the concept of health literacy, notonly from a WHO perspective but also according to various authors. The paperalso analyses the factors influencing the level of health literacy in a population.One of the conclusions of the paper is the need for continuous improvement ofpeople’s health literacy, which nowadays cannot do without institutional andlifelong learning and also efficient use of information technologies.